PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY (CRH) BERBANTUAN APLIKASI CANVA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 10 SURAU GADANG - Risnawati, Debi; Rossa, Rona; Kharisma, Annisa; Farhan Satria, Trinda; Apfani, Sry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mathematics learning outcomes of fourth-grade students at SDN 10 Surau Gadang. The purpose of this study was to determine the effect of the implementation of the Course Review Horay (CRH) learning model assisted by the Canva application on the mathematics learning outcomes of fourth-grade students at SDN 10 Surau Gadang. This research used a quasi-experimental design with The Nonequivalent Posttest-Only Control Group Design. The population of this study consisted of all fourth-grade students at SDN 10 Surau Gadang. The samples used were class IV A as the experimental class and class IV B as the control class. The sampling technique used was total sampling. The data collection technique used a test, with the research instrument in the form of multiple-choice objective test questions. Hypothesis testing used the t-test statistic, preceded by normality and homogeneity tests at a significance level of 0.05. The posttest results showed that the average score of the experimental class (72) was higher than that of the control class (64). The hypothesis testing results showed that tcount = 2.109 and ttable = 1.675, so tcount > ttable, meaning that H0 was rejected and H1 was accepted. The conclusion of this study is that there is an effect of the implementation of the Course Review Horay (CRH) learning model assisted by the Canva application on the mathematics learning outcomes of fourth-grade students at SDN 10 Surau Gadang.